Cryptocurrency; Financial Risk And Shariah-Compliant Alternative Concept - Iman, Aldi Khusmufa Nur; Samsuri, Andriani (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2022)
Some countries consider cryptocurrencies as an avenue for money laundering and other illegal activities, especially Muslim countries, many of which prohibit the use of cryptocurrencies and even prohibit them. This study aims to identify the specific risks of cryptocurrency investment and to understand the sharia-compliant concept to open opportunities for the Islamic economy in the future. The data collection technique used is literature study by collecting data from previous studies in the form of documenting articles, journals or books as well as publication data from other parties. The data analysis techniques used were data reduction, data presentation, and drawing conclusions. The results show that although cryptocurrencies promise some strengths, in terms of investment there is a risk. Some cryptocurrencies have indeed been developed to address the issue of cryptocurrency non-compliance with Sharia law. Like OneGram, one of the cryptocurrencies that can be classified according to sharia. The alternative concept of sharia cryptocurrency has the potential to build Islamic economic products and have a positive effect on the global economy, especially in the context of welcoming a modern Islamic economic order that is conducive to all circles and the realization of a better future for the Islamic economic community